2017
DOI: 10.1176/appi.ajp.2017.16080974
|View full text |Cite
|
Sign up to set email alerts
|

State-Independent and Dependent Neural Responses to Psychosocial Stress in Current and Remitted Depression

Abstract: These findings provide novel evidence regarding the trait and state markers of depression on neural responses to psychosocial stress. Regional activation changes in the ventromedial prefrontal cortex and precuneus may reflect the trait markers of depression. Hyperactivation in the dorsolateral prefrontal cortex and striatum may represent a state-dependent compensatory mechanism during depression remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 36 publications
2
50
0
1
Order By: Relevance
“…To assess the effects of stress, one-sample t -tests were performed in all subjects and in each group. Imaging results were corrected using a family-wise error rate for comparisons (significance at p < 0.05) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of stress, one-sample t -tests were performed in all subjects and in each group. Imaging results were corrected using a family-wise error rate for comparisons (significance at p < 0.05) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The voxel locations of significant MA or pornographic cues activated in two groups ( P FWEcor < 0.05 and k = 30 voxels) were used to create masks for time course extraction, and 6-mm radius spherical regions of interest (ROI) were used to create masks. Using the masks, averaged time courses of multi voxels were calculated from each individual data with MarsBar 0.44 ( http://marsbar.sourceforge.net/ ) and log-roi-batch v2.0 ( http://www.aimfeld.ch/ ) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…All of the participants were native Chinese speakers and screened for history of neurologic, cardiovascular, or psychiatric disease. Previous studies have found altered autonomic and pituitary adrenal responses to stress in humans with major depression (Carroll, Phillips, Hunt, & Der, 2007;Ming et al, 2017). To exclude effects of depression on stress responses, we used the Beck Depression Inventory-II (BDI-II; Beck, Steer, & Brown, 1996) during the screening process (Dedovic et al, 2005), and did not invite participants with scores >14 for participation, since scores above this cutoff indicate the presence of depressive symptomatology (Beck et al, 1996).…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies reported altered stress reactivity in alcohol 44 and nicotine users 45 and elevated levels of anxiety and depression. 46 Cannabis users and controls in our sample were comparable regarding these potential confounders, suggesting specific effects of cannabis dependence on stress reactivity. Both groups exhibited high and comparable performance in the absence of stress indicating comparable baseline cognitive performance.…”
Section: Discussionmentioning
confidence: 53%